Designing communicative spaces – innovative perspectives on teacher education. Issue 1 (2nd January 2017) - Aspfors, Jessica; Valle, Anne Marit
ABSTRACT: The issue of lack of consistency between teacher education and professional practice has been a subject of debate for a long time. In Norway, like many other countries, both scientific communities and governing bodies have put this on the agenda. The current study is qualitative, using a phenomenological-hermeneutical approach. The aim is to deepen the understanding of a communicative space between student teachers and pupils, both face-to-face and online, in order to develop student teachers' interaction competence. The data comprise reflection logs, group interview and video recordings from both live and online meetings with student teachers and pupils, and is analysed by using qualitative content analysis. The findings demonstrate that online communication is different from ordinary classroom communication and therefore student teachers need to interact with pupils online in order to develop these skills. Reflecting on these kinds of situations while still in education helps student teachers to develop their ability to reflect critically on their own practice and prepare them for their future work as teachers.